The Trademark Infringement Caused by Internet Retail Contract Conclusion - Milosavljevic, Nikola (Glasnik Advokatske komore Vojvodine, 2021)
Global development of electronic commerce is currently leading to extensive intellectual property rights violation. In this paper, the author has analyzed the definition of internet retail contract and place where it is concluded, which is the place of possible trademark infringement. Furthermore, there is an overview of electronic sales trademark infringement, and solutions of this problem that have been reached so far. In the end, author presents his opinion on methods that should be used in order to protect trademarks in electronic commerce, taking into account interests of all market participants.